The bacterial neurometabolic signature of the gut microbiota of young children with autism spectrum disorders. Issue 4 (26th March 2020) - Averina, Olga V.; Kovtun, Alexey S.; Polyakova, Svetlana I.; Savilova, Anastasia M.; Rebrikov, Denis V.; Danilenko, Valery N.
Abstract : Introduction. The human gut microbiota is currently seen as an important factor that can promote autism spectrum disorder (ASD) development in children. Aim. This study aimed to detect differences in the taxonomic composition and content of bacterial genes encoding key enzymes involved in the metabolism of neuroactive biomarker compounds in the metagenomes of gut microbiota of children with ASD and neurotypical children. Methodology. A whole metagenome sequencing approach was used to obtain metagenomic data on faecal specimens of 36 children with ASD and 21 healthy neurotypical children of 3–5 years old. Taxonomic analysis was conducted using MetaPhlAn2. The developed bioinformatics algorithm and created catalogue of the orthologues were applied to identify bacterial genes of neuroactive compounds in the metagenomes. For the identification of metagenomic signatures of children with ASD, Wilcoxon's test and adjustment for multiple comparisons were used. Results. Statistically significant differences with decreases in average abundance in the microbiota of ASD children were found for the genera Barnesiella and Parabacteroides and species Alistipes putredinis, B. caccae, Bacteroides intestinihominis, Eubacterium rectale, Parabacteroides distasonis and Ruminococcus lactaris . Average relative abundances of the detected genes and neurometabolic signature approach did not reveal many significant differences in the metagenomes of the groups that were compared. We noted decreases in the abundance of genes linked to production of GABA, melatonine and butyric acid in the ASD metagenomes. Conclusion. For the first time, the neurometabolic signature of the gut microbiota of young children with ASD is presented. The data can help to provide a comparative assessment of the transcriptional and metabolomic activity of the identified genes.